2017
DOI: 10.1007/s00709-017-1134-8
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin localizes to plant intra/extracellular peripheries of highly specialized cells involved in pollen-pistil interactions

Abstract: Calcium (Ca2+) plays essential roles in generative reproduction of angiosperms, but the sites and mechanisms of Ca2+ storage and mobilization during pollen-pistil interactions have not been fully defined. Both external and internal Ca2+ stores are likely important during male gametophyte communication with the sporophytic and gametophytic cells within the pistil. Given that calreticulin (CRT), a Ca2+-buffering protein, is able to bind Ca2+ reversibly, it can serve as a mobile store of easily releasable Ca2+ (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Previous work from our laboratory provided evidence that CRT may be involved in Ca 2+ homeostasis and molecular chaperoning during the key reproductive events in Petunia pistil, such as pistil transmitting tract maturation, pollen-pistil interactions, double fertilization, and early embryogenesis [ 17 , 18 , 22 ]. We also demonstrated that CRT has a critical role in pollen tube growth in vitro [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work from our laboratory provided evidence that CRT may be involved in Ca 2+ homeostasis and molecular chaperoning during the key reproductive events in Petunia pistil, such as pistil transmitting tract maturation, pollen-pistil interactions, double fertilization, and early embryogenesis [ 17 , 18 , 22 ]. We also demonstrated that CRT has a critical role in pollen tube growth in vitro [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, localization of this protein outside the ER has also been observed in eukaryotic cells. Plant CRT was detected in many different compartments and structures, including dictyosomes, vesicles, protein bodies, nucleus, plasma membrane, and the cell wall [ 22 ]. Although, some previous work from our lab and others indicated location of CRT in several extracellular regions were somewhat controversial, an elegant work of Luczak et al [ 34 ] provided clear evidence that CRT, similar to several other proteins, is present in the cell walls of few plant species including maize, Lupinus and Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A C-terminally truncated calreticulin was observed (CaCl 2 spot 1274). Although regarded as an ER-resident protein, calreticulin was described in other subcellular compartments [43]. Animal calreticulin is linked with the recognition of tumor and apoptotic cells, and wound healing in plants it is linked to growth and stress responses [44].…”
Section: Resultsmentioning
confidence: 99%